APLIKASI PENGEMBANGAN HUMAN CAPITAL MELALUI PELATIHAN MANAJEMEN PERSEDIAAN DAN MANAJEMEN KEUANGAN PADA INDUSTRI KECIL MENENGAH DI DESA DATARAN BULAN KABUPATEN TOJO UNA-UNA - Husnah Husnah; Erwan Sastrawan; Rosida P Adam; Muh. Thaib; Rahmatio Rahmatio (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Problems in general are related to the development of IKM in Indonesia, one of which is related to the low human capital owned by IKM actors in managing their businesses, so that this service program aims to provide motivation, knowledge and skills for business management, specifically in Inventory Management and Financial Management in Indonesia. IKM in Plain Bulan, Tojo Unauna Regency. This goal is achieved through training methods by transferring knowledge, discussing and simulating cases. The target audience for IKM Services and IKM Agriculture in Sukamaju Village, Dataran Bulan, Tojo Unauna Regency is 25 people. Implementation time in June. With research outputs in the form of articles published in local journals, and activity documentation.